Antimicrobial and UV Blocking Properties of Composite Chitosan Films with Curcumin Grafted Cellulose Nanofiber. (March 2021) - Zhang, Xinhui; Li, Yintao; Guo, Mingming; Jin, Tony Z.; Arabi, Saifanassour Ali; He, Qiao; Ismail, Balarabe B.; Hu, Yaqin; Liu, Donghong
Abstract: Chitosan has attracted much attention for use in antimicrobial food packaging because of its unique antibacterial properties and excellent film-forming ability. However, its poor barrier properties to UV light and high water-solubility limit its application. In this study, modified cellulose nanofiber was incorporated into chitosan films to improve their UV blocking, physical, and antibacterial properties. Modified cellulose nanofiber was obtained by grafting curcumin to 2, 2, 6, 6-tetramethylpiperidine-1-oxyl (TEMPO)-oxidized cellulose. Infrared spectroscopy and X-ray photoelectron spectroscopy results indicated that cellulose was successfully modified. Bio-nanocomposite films composed of chitosan (67–100 wt %) and curcumin grafted TEMPO-oxidized cellulose nanofiber (CGTOCNF, 0–33 wt %) were prepared using the casting method. Scanning electron microscopy images and X-ray diffraction analysis showed that the addition of CGTOCNF noticeably affected the morphology of the composite films, with the crystallinity significantly increasing from 21.93% to 87.15%. Moreover, CGTOCNF incorporation improved the oxidation resistance and UV blocking properties of the composite films compared to pure chitosan films. It is also worth mentioning that all of the composite films have excellent antibacterial activity with CGTOCNF partially replacing chitosan. Furthermore, the water solubility of films decreased with the incorporation of CGTOCNF. However, this study demonstrated that incorporation of CGTOCNF at concentrations greater than 10% resulted in a slight decrease in the water vapor barrier properties and mechanical strength of chitosan films. The findings in this work indicate that the addition of 10% CGTOCNF to chitosan films enhances their physical and antibacterial properties, thus increasing their potential for use in food packaging. Graphical abstract: Image 1 Highlights: Curcumin was grafted into cellulose nanofiber (CGTOCNF) via ester bond. CGTOCNF incorporation enhanced the UV shielding property of chitosan films. The composite films had lower water solubility than pure chitosan films. CGTOCNF did not affect the antibacterial and mechanical properties of films. The composite films have potential to be used as biodegradable food packaging.